Research Trend of Socio Scientific Issues (SSI) in Physics Learning Through Bibliometric Analysis in 2011-2020 using Scopus Database and the Contribution of Indonesia - Utama Alan Deta; Arika Arika; Dhila Linggar Lentika; Suliyanah Suliyanah; Setyo Admoko; Nadi Suprapto; Sayyidah Annimatus Sa’diyah Al Lathifah (Postgraduate, University of Mataram, 2021)
Socio-Scientific Issues (SSI) are controversial topics that have a scientific basis and important to society. This study aims to analyze the trends of SSI research publications from 2011-2020, visualize SSI research trends and how Indonesian researchers contribute to SSI research. This study was conducted on April 18, 2021, using bibliometric analysis. Data obtained is 225 data and taken by using Scopus database with